Crimmigrant Nations : Resurgent Nationalism and the Closing of Borders - Woude, Maartje Amalia Hermina van der, 1980-; Koulish, Robert E. (Robert Edwin) (Book collections on Project MUSE., 2020)
As the distinction between domestic and international is increasingly blurred along with the line between internal and external borders, migrants--particularly people of color--have become emblematic of the hybrid threat both to national security and sovereignty and to safety and order inside the state. From building walls and fences, overcrowding detention facilities, and beefing up border policing and border controls, a new narrative has arrived that has migrants assume the risk for government-sponsored degradation, misery, and death. Crimmigrant Nations examines the parallel rise of anti-immigrant sentiment and right-wing populism in both the United States and Europe to offer an unprecedented look at this issue on an international level. Beginning with the fears and concerns of immigration that predate the election of Trump, the Brexit vote, and the signing and implementation of the Schengen Agreement, Crimmigrant Nations critically analyzes nationalist state policies in countries that have criminalized migrants and categorized them as threats to national security. Highlighting a pressing and perplexing problem facing the Western world in 2020 and beyond, this collection of essays illustrates not only how anti-immigrant sentiments and nationalist discourse are on the rise in various Western liberal democracies, but also how these sentiments are being translated into punitive and cruel policies and practices that contribute to a merger of crime control and migration control with devastating effects for those falling under its reach. Mapping out how these measures are taken, the rationale behind these policies, and who is subjected to exclusion as a result of these measures, Crimmigrant Nations looks beyond the level of the local or the national to the relational dynamics between different actors on different levels and among different institutions.